Effectiveness of Giving Black Soldier Fly Maggot Flour in Basal Rations on the Quality of Quail (Coturnix-coturnix Japonica) Eggs - Putri Rotua br. Harianja; Usman Budi; Nurjama'yah br Ketaren; Wendi Hutajulu (Talenta Publisher, 2024)
Protein is a nutrient that need by quail for gowing. However it price is expensive so it is necessary to look for alternatives. This study aims to determine the effectiveness of Black Soldier Fly (BSF) maggot flour as a substitute for fish meal thus protein alternatives. The study design was carried out experimentally using a completely randomized design (CRD) with 4 treatments, namely P0 = ration without BSF Maggot Flour, P1 = Basal ration with 15% BSF maggot flour, P2 = Basal ration with 20% BSF maggot flour, P3 = Basal ration with 25% BSF maggot flour, each treatment had 5 replications. The research parameters were egg weight, egg white index, egg yolk index, and haugh units. The results showed that there was a real influence on egg weight and egg yolk index. However, it did not show a real influence on the egg white index and haugh unit. The use of a basal diet with 25% BSF maggot flour showed better results than treatment with a lower dose. In conclusion that basal rations and BSF maggot flour as much as 25% are suitable for use as quail (Coturnix-Coturnix Japonica) feed to increase the quality value of quail eggs.